Analisis Kesesuaian Rancangan Perencanaan Pembelajaran Terhadap Kurikulum Tingkat SMK - Mesiono, Mesiono; Suciyandhani, Adinda; Hasibuan, Rolin Fadilah (Jurnal Ilmiah Wahana Pendidikan, 2023)
The world of education continues to develop along with the times, this development aims to improve the quality of education, especially in Indonesia. One of the important changes that have occurred in the world of education in Indonesia is changes to the curriculum. We already know that changes to the curriculum are also followed by changes to learning tools, one of which is the RPP. In order to implement the learning program that has been outlined in the syllabus, the teacher must prepare a Learning Implementation Plan (RPP). The RPP is a guide for teachers in carrying out learning both in the classroom, laboratory and field for each basic competency.